Clinical questionnaires for chronic obstructive pulmonary disease diagnosis: A systematic review and meta-analysis - Alirio Rodrigo Bastidas-Goyes; Andrés Orlando Cardozo-Niño; Elías Quintero-Muñoz; Kenny Andrés López-Gómez; Lilia Patricia Suárez-Escobar; Lorena Esmeralda Hernández-Santos (Revista de la Facultad de Medicina)
Introduction: The use of early screening questionnaires for chronic obstructive pulmonary disease (COPD) in primary health care could improve underdiagnosis. Several instruments are currently available, but there is scant information on their diagnostic performance.